Stable incidence of surgical treatment and hospitalisation for humeral shaft fractures among 0- to 16-year-old patients in Finland from 1987 to 2010. (March 2014) - Salonen, A.; Pajulo, O.; Lahdes-Vasama, T.; Mattila, V. M.
Background: Studies among children experiencing fractures report an increasing trend toward operative management. In the present study, we examined whether the same trend has occurred for humeral shaft fractures in accordance with increasing interest toward intramedullary nailing and other operative treatments. The number, incidence and treatment of all hospitalised 0- to 16-year-old patients with humeral shaft fractures in Finland was assessed over a recent 24-year period. Method: The study included the entire adolescent (0–16 years) population in Finland during the 24-year period from January 1, 1987, to December 31, 2010. Data on hospitalised patients who sustained humeral shaft fractures were obtained from the nationwide National Hospital Discharge Register (NHDR) of Finland. Results: During the study period, there were a total of 1, 165 hospitalisations with a main or secondary diagnosis of humeral shaft fracture. The incidence of hospitalisation due to humeral shaft fractures was 4.8 per 100, 000 person-years. The incidence increased only slightly among girls from 3.3 per 100, 000 person-years in 1987 to 5.3 per 100, 000 person-years in 2010. The incidence of reposition and casting was 1.1 per 100, 000 person-years and the incidence of reposition with osteosynthesis, including intramedullary nailing, was 1.4 per 100, 000 person-years. The specific incidence of intramedullary nailing remained low with no signs of increased incidence, and the incidence was 0.3 per 100, 000 person-years. There were no significant changes in the incidence of surgical treatment during the 24-year study period. Conclusion: Despite an overall increasing trend toward operative management of fractures in children, conservative management remains the treatment of choice for humeral shaft fractures based on the low and steady incidence of surgical treatment during the 24-year study period. In addition, the incidence of hospitalisation for fractures remained low without a significant increase during the study period.